Effect of chop length and level of dry matter on fermentation and nu-tritive value of ensiled corn stover - Saeed, Ali A. (Journal of Kerbala for Agricultural Sciences, 2017)
This study was aimed to investigate the effect of chop length (1-1.5 or 2-2.5 cm) and dry matter (DM) levels (25, 30, 35 or 40%) on fermentation of corn stover silage and its nutritive value. Chopped samples were pretreated with 1% urea and 8% of date's honey and ensiled for 60 days. Results showed an increase (P˂0.01) in DM content with increasing chop length in association with a 0.96% decrease in ether extract (EE) content. According to fermentation characteristics, all samples were good quality; pH values ranged 3.73-4.33 for the lowest and highest levels of DM respectively. Concentrations of ammonia nitrogen (NH3-N) were below 0.5% of total nitrogen (TN). Lower pH (P˂0.01) was recorded in samples of stover ensiled with fine chop length (FCSS), but it was characterized with higher NH3-N concentrations as compared with those ensiled with coarse length (CCSS) (3.99 and 0.43 vs. 4.08, 0.33 % of TN, respectively). Results also showed higher (P˂0.01) DM loss in FCSS (15.58 vs. 10.99%), however, it was 30 hours more (P˂0.01) resistant to aerobic spoilage as compared with CCSS, moreover, it was prior (P˂0.05) in in vitro DM and organic matter (OM) digestibilities (IVDMD and IVOMD). Quality parameters were affected by DM contents of ensiled materials, where, there was a significant increase (P˂0.01) in DM loss and a decrease (P˂0.01) in resistance to aerobic deterioration. Values of buffering capacity (BC) were increased (P˂0.05) with increasing DM levels, higher values of 113.11 Meq. NaOH/100 g DM was estimated in 40% level of DM. This level was correlated with lower (P˂0.01) IVDMD, 57.87% and IVOMD, 60.73%. Good quality of corn stover silage samples in this study was confirmed by high Fleig point values of about 86-90.